Factors associated with mortality from variceal upper gastrointestinal bleeding - Olga Magdalena Moreira Barinaga; Zenén Rodríguez Fernández; Ernesto Manzano Horta; Sinuhé Rodríguez Hung; Lázaro Ibrahim Romero García; Isabel Maurelo Martínez-Pinillo (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Variceal upper gastrointestinal bleeding constitutes a clinical surgical problem that still has an excessively high mortality. Objective: To estimate the burden of mortality and its causes related to the disease, as well as the associated factors according to selected variables.  Material and Methods: An observational, descriptive, and cross-sectional study was conducted in 39 patients who were admitted with this diagnosis to the General Surgery Service of the "Saturnino Lora" Teaching Provincial Hospital of Santiago de Cuba during 2013-2016. Results: Middle-aged male patients with several associated risk factors predominated in the study.  Child-Pugh Class B and Classes II and III bleedings were the most frequent ones. The diagnosis was eminently clinical.  Endoscopic treatment was carried out in three patients and the application of the Sengstaken-Blakemore tube was infrequent. 7 patients received surgical treatment, who account for the 43,8% of those who died. Mortality rate ranged from 22,2% in 2013 to 41,0% in 2016. Conclusions: The persistence of variceal upper gastrointestinal bleeding responds to the poor use of endoscopic treatment and the non-use of somatostatin derivates.  It is also associated with high levels of mortality, and in close relationship with a grade of advanced hepatic failure and urgent interventions.  There was a correspondence between the direct causes of death and the disease under analysis.   Keywords: Portal hypertension, variceal upper gastrointestinal bleeding, esophagogastric varices, medical treatment, endoscopy, surgery.